2023
DOI: 10.1002/pen.26319
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical behavior of three dimensionally printed fabric structures

Abstract: Additive manufacturing of fabrics is an emerging research topic with potential applications in several industries including high performance wearable products and high‐temperature textiles. Therefore, thermal, mechanical, and viscoelastic properties of such fabrics need to be determined. In this research, the thermomechanical behavior of additively manufactured plain weave fabrics at and above glass transition temperature (Tgtrue) is studied. The time‐dependent mechanical response using a viscoelastic material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The results showed that a well-designed gradient distribution improves the material's in-plane performance. Additionally, multi-scale methods have found positive applications in aspects such as the thermal performance, 26,27 curing process, 28 and performance degradation 29,30 of composite materials. Multiscale analysis provides a foundational framework for further research into 3D woven composites, such as constitutive model parameters for homogenized models under external impact [31][32][33] and training datasets for machine learning from extensive simulation data.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a well-designed gradient distribution improves the material's in-plane performance. Additionally, multi-scale methods have found positive applications in aspects such as the thermal performance, 26,27 curing process, 28 and performance degradation 29,30 of composite materials. Multiscale analysis provides a foundational framework for further research into 3D woven composites, such as constitutive model parameters for homogenized models under external impact [31][32][33] and training datasets for machine learning from extensive simulation data.…”
Section: Introductionmentioning
confidence: 99%
“…16 The increase in steady-state temperature is regarded as a precursor of fatigue failure of rubber materials, 17 and the higher temperature could make the rubber material age and shorten the fatigue life. 18,19 The hysteresis temperature rise will cause surface fatigue shedding, abrasive wear, plastic deformation, cracks, and even fracture damage in the rubber roller, 20,21 as shown in Figure 1, so that they need to be replaced frequently, thus increasing the production cost. In addition, the loading frequency and cycle in the mechanical loading process, the fillers and additives in the rubber formula, the ambient temperature, and humidity will affect the fatigue life of the rubber material.…”
Section: Introductionmentioning
confidence: 99%